2016
DOI: 10.1002/chir.22580
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Thermodynamics of Chiral Recognition in Bile Salt Micelles

Abstract: Isothermal titration calorimetry (ITC) is shown to be a sensitive reporter of bile salt micellization and chiral recognition. Detailed ITC characterization of bile micelle formation as well as the chiral recognition capabilities of sodium cholate (NaC), deoxycholate (NaDC), and taurodeoxycholate (NaTDC) micelle systems are reported. The ΔH(demic) of these bile salt micelle systems is directly observable and is strongly temperature-dependent, allowing also for the determination of ΔCp(demic). Using the pseudo-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In recent work, the difference in the enthalpy of binding of R‐ vs. S‐BNDHP to bile salts was measured to be about 1 kJ per mole, whereas it was not possible to detect the difference in the enthalpy of binding of R‐ vs. S‐BN to bile aggregates . Whereas Figure showed that weak intermoleculear NOEs could be observed for R,S‐BNDHP binding to respective edge locations of bile acid aggregates, it was not possible to detect NOEs from R,S‐BN to the bile carbon‐7 or carbon‐12 edges, which is consistent with weaker binding of R,S‐BN to bile aggregates.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In recent work, the difference in the enthalpy of binding of R‐ vs. S‐BNDHP to bile salts was measured to be about 1 kJ per mole, whereas it was not possible to detect the difference in the enthalpy of binding of R‐ vs. S‐BN to bile aggregates . Whereas Figure showed that weak intermoleculear NOEs could be observed for R,S‐BNDHP binding to respective edge locations of bile acid aggregates, it was not possible to detect NOEs from R,S‐BN to the bile carbon‐7 or carbon‐12 edges, which is consistent with weaker binding of R,S‐BN to bile aggregates.…”
Section: Resultsmentioning
confidence: 93%
“…[7][8][9][10][11][12] Despite the fact that the majority of carbon atoms in bile acids such as cholate and deoxycholate exhibit exclusive chirality in nature, the potential physiological significance of bile acid guest-host chiral recognition remains unknown. Recently, the thermodynamics of chirally selective guest-host binding have been characterized by isothermal titration calorimetry, 13 but the structural mechanism by which bile aggregates selectively interact with enantiomers of guest compounds is not known.…”
mentioning
confidence: 99%
“…23 The ΔH demic of these bile salt micelle systems is observable and strongly temperature dependent, allowing the determination of ΔCp demic . Timothy G. Strein et al reported on the application of ITC to the process of bile salt demicellization (demic in short) and its chiral binding recognition.…”
Section: Guest-host Chiral Binding Interactionsmentioning
confidence: 99%
“…Timothy G. Strein et al reported on the application of ITC to the process of bile salt demicellization (demic in short) and its chiral binding recognition. 23 The ΔH demic of these bile salt micelle systems is observable and strongly temperature dependent, allowing the determination of ΔCp demic . The chiral selectivity of guest-host binding of model chiral racemic compounds to the bile salt micelles was investigated.…”
Section: Guest-host Chiral Binding Interactionsmentioning
confidence: 99%
“…[16] The primary micelles of bile acid salts at lower temperatures are formed due to hydrophobic effect (movement of water molecules, during the association, from the convex hydrophobic surface of the monomer into the interior of the solutionentropically driven), whereas at higher temperatures, the micelles are formed due to hydrophobic interactions between the convex surfaces of the steroid skeleton (enthalpically driven). [17,18] Kawamura et al gave a model similar to Small, where bile acid anions were aligned on the surface of the disc in such a manner that the orientation of the carboxylate groups (down, up) was successively changed, giving minimal electrostatic repulsions. [19] At concentrations several times higher than the CMC (for some bile acid anions), the primary micelles are bonded to each other by hydrogen bonds-Small's secondary micelles.…”
Section: Introductionmentioning
confidence: 99%